2019
DOI: 10.1039/c9gc02949d
|View full text |Cite
|
Sign up to set email alerts
|

A roadmap for renewable C2–C3 glycols production: a process engineering approach

Abstract: A review of strategies and challenges for chemical and biochemical production and purification of C2–C3 glycols from renewable sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 229 publications
0
64
0
Order By: Relevance
“…101 In contrast, this technique is non-environmentally friendly and gives a low yield of production. 102 In 2019, the global market size of 1,3-PDO exceeded USD 490 million, which was approximately two-thirds that of conventional PTT production. 103 Thus, an emerging bio-based 1,3-PDO from a renewable source, specifically glycerol, is enticing and profitable.…”
Section: Global Market Of Biochemical Production From Glycerolmentioning
confidence: 99%
“…101 In contrast, this technique is non-environmentally friendly and gives a low yield of production. 102 In 2019, the global market size of 1,3-PDO exceeded USD 490 million, which was approximately two-thirds that of conventional PTT production. 103 Thus, an emerging bio-based 1,3-PDO from a renewable source, specifically glycerol, is enticing and profitable.…”
Section: Global Market Of Biochemical Production From Glycerolmentioning
confidence: 99%
“…Among the various substrates and products that we evaluated, we identi ed that ethylene glycol (EG) was a highly promising substrate for orthogonal production of a variety of chemicals because it minimized the interactions between biomass and chemical producing pathways. Today, EG is produced primarily by the petrochemical industry from ethylene, however, renewable alternatives are currently in the early stages of development (31,32). In particular, EG can be produced from the electrochemical conversion of CO 2 (11,13), as well as from the chemocatalytic conversion of cellulosic materials and glycerol (a common waste in industrial biofuel and soap production) (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Today, EG is produced primarily by the petrochemical industry from ethylene, however, renewable alternatives are currently in the early stages of development (31,32). In particular, EG can be produced from the electrochemical conversion of CO 2 (11,13), as well as from the chemocatalytic conversion of cellulosic materials and glycerol (a common waste in industrial biofuel and soap production) (31,32). Thus, though unconventional as a feedstock, EG could serve as a replacement for glucose in the modern bioprocess.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various substrates and products that we evaluated, we identified that ethylene glycol (EG) was a highly promising substrate for orthogonal production of a variety of chemicals because it minimized the interactions between biomass and chemical producing pathways. Today, EG is produced primarily by the petrochemical industry from ethylene, however, renewable alternatives are currently in the early stages of development [11,12]. In particular, EG can be produced from the electrochemical conversion of CO 2 [13,14], from the chemocatalytic conversion of cellulosic materials and glycerol (a common waste in industrial biofuel and soap production) [11,12], as well as from the depolymerization of poly(ethylene terephthalate) (PET) plastic (an abundant waste material) to its monomers [15][16][17][18].…”
mentioning
confidence: 99%
“…Today, EG is produced primarily by the petrochemical industry from ethylene, however, renewable alternatives are currently in the early stages of development [11,12]. In particular, EG can be produced from the electrochemical conversion of CO 2 [13,14], from the chemocatalytic conversion of cellulosic materials and glycerol (a common waste in industrial biofuel and soap production) [11,12], as well as from the depolymerization of poly(ethylene terephthalate) (PET) plastic (an abundant waste material) to its monomers [15][16][17][18]. Thus, though unconventional as a feedstock, EG could serve as a sustainable and/or renewable replacement for glucose in the modern bioprocess.…”
mentioning
confidence: 99%